STRATEGI MENGATASI TRAUMA PADA KORBAN BULLYING MELALUI KONSELING EKSISTENSIAL - Syafrianto Tambunan; Mulkiyan Mulkiyan (Universitas Islam Ahmad Dahlan, 2021)
Bullying is a behavior that does not please those who feel it and makes people tend to be someone who has a closed nature or is more aloof from the crowd. In recent years there have been many cases of bullying that have occurred and this has experienced an increase in its spread to the extent that it has a negative impact on the sufferer, namely a sense of trauma that arises until it is sustainable and for quite a long time. Trauma is a nature in which the victim will feel a sense of anxiety, anxiety, emotions and behavior that lose control and fear appears instantly. As for problems like this, they must be addressed as soon as possible because they are afraid that they will get worse and the methods of alleviation will also vary and allow problems to arise in daily life. The strategy used is existential counseling in which there are several concepts, namely trauma, bullying, some signs of bullying, the impact of bullying, the existential counseling process, the goals of existential counseling, the function and role of the counselor, the role of the client in counseling, how the client's relationship with the counselor in counseling activities, and how to overcome trauma in existential counseling.